Examining the use of LEGO Serious Play to enhance postgraduate research capacity - Idris Olayiwola Ganiyu; Gosia Plotka; Patrice Seuwou; Adejoke Ige-Olaobaju (Humanities & Social Sciences Communications)
Abstract The use of LEGO Serious Play as a tool to enhance postgraduate research capacity is an emerging concept that has gained attention in recent years. This hands-on, interactive approach to learning and problem-solving has been utilised in a variety of fields and industries, but its potential in the realm of postgraduate research is still being explored. One of the main challenges faced by postgraduate students is the ability to think critically and creatively in their research projects. These challenges may be connected to the traditional teaching methods in postgraduate research, such as lectures and seminars, which often focus on theoretical concepts and do not provide students with practical tools to apply these concepts in their research. This can result in students feeling disconnected from their work and lacking the skills and confidence to think outside the box. This study examined the use of LEGO Serious Play to enhance postgraduate research capacity. A quantitative research approach was adopted for data collection and analysis. A simple random sampling technique was employed to select a cross-section of postgraduate students who participated in this study for data collection. Partial least squares structural equation modelling using SmartPLS 4.0 was employed to test the mediating influences of pedagogical technique and postgraduate students’ research capacity on the relationship between LEGO Serious Play and research outcome. The finding revealed that LEGO Serious Play exerts a significant positive influence on pedagogical technique. The implication for practice which emerged from the outcome of the statistical analysis is presented in this study.